The PTI to ETI Continuum in Phytophthora-Plant Interactions - Naveed, Zunaira Afzal; Wei, Xiangying; Chen, Jianjun; Mubeen, Hira; Ali, Gul Shad (Frontiers in Plant Science, 2020)
Phytophthora species are notorious pathogens of several economically important crop plants. Several general elicitors, commonly referred to as Pathogen-Associated Molecular Patterns (PAMPs), from Phytophthora spp. have been identified that are recognized by the plant receptors to trigger induced defense responses in a process termed PAMP-triggered Immunity (PTI). Adapted Phytophthora pathogens have evolved multiple strategies to evade PTI. They can either modify or suppress their elicitors to avoid recognition by host and modulate host defense responses by deploying hundreds of effectors, which suppress host defense and physiological processes by modulating components involved in calcium and MAPK signaling, alternative splicing, RNA interference, vesicle trafficking, cell-to-cell trafficking, proteolysis and phytohormone signaling pathways. In incompatible interactions, resistant host plants perceive effector-induced modulations through resistance proteins and activate downstream components of defense responses in a quicker and more robust manner called effector-triggered-immunity (ETI). When pathogens overcome PTI—usually through effectors in the absence of R proteins—effectors-triggered susceptibility (ETS) ensues. Qualitatively, many of the downstream defense responses overlap between PTI and ETI. In general, these multiple phases of Phytophthora-plant interactions follow the PTI-ETS-ETI paradigm, initially proposed in the zigzag model of plant immunity. However, based on several examples, in Phytophthora-plant interactions, boundaries between these phases are not distinct but are rather blended pointing to a PTI-ETI continuum.